1998
DOI: 10.1029/97jb03010
|View full text |Cite
|
Sign up to set email alerts
|

Rate and state of background stress estimated from the aftershocks of the 1989 Loma Prieta, California, earthquake

Abstract: Abstract. Estimates of the tectonic stress state including loading rate and magnitude of background stress are derived from the spatial and temporal distribution of Loma Prieta aftershocks. This technique was previously applied to the Landers aftershock sequence [Gross and Kisslinger, 1997] and is based upon the seismicity model of Dieterich [1994]. Dieterich's theory suggests that background seismicity should be proportional to stress rate and the number of aftershocks in an area should be proportional to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
2
31
1
Order By: Relevance
“…DIETERICH (1994) has derived Omori's law from the equations of rate-and-state friction. GROSS and BURGMANN (1998) have applied this result to the Loma Prieta earthquake and its application has been discussed by ZIV and RUBIN (2003). There is clearly a close association between this work and the damage mechanics approach.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…DIETERICH (1994) has derived Omori's law from the equations of rate-and-state friction. GROSS and BURGMANN (1998) have applied this result to the Loma Prieta earthquake and its application has been discussed by ZIV and RUBIN (2003). There is clearly a close association between this work and the damage mechanics approach.…”
Section: Discussionmentioning
confidence: 72%
“…In the simplest dislocation model of an earthquake, the strain accumulation and release produces regions of stress increase (DAS and SCHOLZ, 1981a,b). These stress ''halos'' certainly contribute to the occurrence of aftershocks (TODA et al, 1998;GROSS and BURGMANN, 1998;RYBICKI, 1973;MENDOZA and HARTZELL, 1988;KING et al, 1994;MARCELLINI, 1995;HARDEBECK et al, 1998;STEIN, 1999). However, the actual stress fields prior to and after an earthquake are undoubtedly very complex.…”
Section: Introductionmentioning
confidence: 99%
“…2), with large-scale and small-scale heterogeneity in the physical properties and associated stress fields, where continuous aseismic creep takes place (e.g., SIBSON, 1986;RICE, 1992;GUDMUNDSSON, 1993;FJÄ DER et al, 1994). Seismic zones are also subject to changes in fluid pressure and permeability, which affect the associated seismicity (e.g., SIBSON, 1981SIBSON, , 1994SIBSON, , 1996BYERLEE, 1993;WOLF et al, 1997;GROSS and BÜ RGMANN, 1998). These complexities in the infrastructure and stress fields of seismic zones significantly decrease the probability of successful prediction of most earthquakes.…”
Section: Seismic Zones Fault Zones and Earthquake Predictionmentioning
confidence: 99%
“…If the fault plane is subject to high fluid pressure during faulting, of which there is abundant evidence (e.g., RICE, 1992;BYERLEE, 1993;GROSS and BÜ RGMANN, 1998), then v s $0 and the condition of eq. (2) becomes c :2T 0 .…”
Section: Figurementioning
confidence: 99%
“…Dieterich's aftershock model has been used to assess probabilistic seismic hazards (Toda et al, 1998(Toda et al, , 2002, estimate the tectonic stressing rate from the spatiotemporal evolution of Loma Prieta aftershocks (Gross and Burgmann, 1998) and infer stress change due to dike intrusion in the Kilauea volcano in Hawaii (Dieterich et al, 2000). These studies have demonstrated that this model has (Huang et al, 2008;Zhu et al, 2008;Zhao et al, 2010).…”
Section: Dieterich's Aftershock Modelmentioning
confidence: 99%